An effective population size for reliable map resolution of coconut (Cocos nucifera L.) - C. K. Bandaranayake (International Coconut Community Journal, 2006)
Size of the mapping population is a critical landmark in producing a genome map of any crop. In coconut there is difficulty in producing a reasonably large mapping population within a specified period of time. Therefore revealing an effective population size for standard map resolution of coconut is needed. It is found that the size of a segregating population with 400 individuals is efficient for consistent map resolution of coconut.